The visual world of French theory figurations - Wilson, Sarah 1956- (Yale University Press, 2010)
"This book ... focuses on a remarkable series of encounters between the most prominent French philosophers of the 1960s and 1970s-- Sartre, Deleuze, Bourdieu, and Foucault among them-- and the artists of their times, most particularly the protagonists of the Narrative Figuration movement. Each encounter involved either a mutual engagement or the writing of critical texts or catalogue prefaces-- texts that illuminate not only the work of the artists but also the production of the philosopher-writer concerned"--Publisher's description